Alternative Perovskites for Photovoltaics. Issue 21 (26th April 2018) - Jodlowski, AlexanderD.; Rodríguez‐Padrón, Daily; Luque, Rafael; de Miguel, Gustavo
Abstract: The discovery of unique optoelectronic properties of 3D ABX3 perovskites has produced a great impact on the field of photovoltaics. In the initial years after the breakthrough, interest has focused on a limited number of 3D ABX3 perovskite materials, including the archetypal CH3 NH3 PbI3 and its counterparts. Undoubtedly, the main limitation of perovskite devices is their low stability due the fast degradation of the perovskite layer; however, the high toxicity of Pb also poses a concern. Herein, the recent increasing number of articles reporting the theoretical modeling, synthesis, optoelectronic characterization, and implementation of alternative perovskite materials in solar devices is summarized. The extensive variety of perovskite derivatives is classified according to the material dimensionality and the crystal structure. The particular strengths and weaknesses for each novel material are discussed, and the device performance and potential stability enhancements are also highlighted. Abstract : The main limitation of perovskite devices are their low stability due the fast degradation of the perovskite layer and the high toxicity of Pb. The extensive variety of alternative perovskites for solar devices is summarized in this review highlighting the strengths and weaknesses for each material.